Práticas de bullying escolar e a inclusão educacional: a formação de professores nesse contexto - Sarzi, Luana Zimmer (2014)
This research is part of a line of research in the Special Education Graduate Program of Federal University of Santa Maria - UFSM. Sought to reflect and draw together a group of teachers from a state school in Santa Maria - RS, strategies for mitigation practices of school bullying aimed at the educational inclusion of their students. The investigation occurred from a qualitative methodology, focusing on Action Research (Carr and Kemmis, 1988), who guided the fellowship process of teacher training so as to raise the rethinking of practices and the creation of alternatives for the recognition and reduction practices of school bullying. The theoretical features of this research allow the analysis and understanding of the concept of educational inclusion studies by Garcia (2008), as a result, we seek to conceptualize school bullying and its protagonists , with the support of authors such as: Fante (2005), Guareschi (2008), Silva (2010), Alkimin (2011) and Silva (2013 ). And , with authors such as Freire (1996), Gómez (1998) and Pimenta (2005) sought to understand what processes of training teacher that are in this type of violence in a space consisting of a diversity of people, knowledge and practices. The main results are in the form of lines of analysis and rush on discussions about the importance of training teachers for the recognition of school bullying, as well as the establishment of strategies for minimizing these practices. Through dialogical meetings with the group of teachers participating in the research, it was possible to observe how the bullying constitutes at school where they work, what are the main cases of such violence. Different activities proposed for the minimization nine specific cases of bullying were identified in the school with two students with Special Educational Needs, assisted in the resource room, as well as Accordingly, based on the activities undertaken by teachers, in addition to discussions during the meetings were elected, in the form of conclusion, indicators for the minimization of the practices of school bullying that enhance educational inclusion. To hear what students have to say about the practice of bullying. Thus, the experiences become revealed and become susceptible to interventions; To develop a work that manage the control of aggressiveness, tolerance, respect for differences and individualities of each; To reframe the teaching practice, when necessary, in order to ensure that students leave the passivity and become agents of their own learning and active participants as subjects in combating bullying; Enlighten students about what constitutes bullying in the school, what are the characteristics of bullying and who the characters are; Continuing education of teachers in order to understand that in their practice, constant discussions and reflections in order to pursue new strategies and methodological alternatives that maya fight school bullying